If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(4x-3)-8=4+2
We simplify the equation to the form, which is simple to understand
2(4x-3)-8=4+2
Reorder the terms in parentheses
+(+8x-6)-8=4+2
Remove unnecessary parentheses
+8x-6-8=+4+2
We move all terms containing x to the left and all other terms to the right.
+8x=+4+2+6+8
We simplify left and right side of the equation.
+8x=+20
We divide both sides of the equation by 8 to get x.
x=2.5
| 9-3w=-2+4w | | 52-(2x+7)=2(x+5)+5 | | 52-(2x+7)=2(x+5)+5solve | | 5x+3=3x-17 | | x^2+5x-915=0 | | 0.10x+.05(4-x)=.10(1) | | (3x-3)=16-(-7+x) | | 3(4-10y)=8(8y+16) | | 6k-3(2k-3)= | | -3(2s-6)-18=2(6s+7)-2 | | 27750+200x=312.50x | | 3(z-22)=36-3(z-2) | | 2x+6=-3-x | | 11x-11=5x-8 | | 2x+3=-4 | | 8(9x-10)+10=7x+6 | | 42x=966 | | 8x-(4x+6)=22 | | 18x=24 | | 1x=24 | | -8x=-7 | | 2(10)+6= | | 27750+200x=50000 | | 27750+200=50000 | | 4(x+5)=2(2x+4)+12 | | 10*x=100 | | 23=x^1*(15)+x^2*(20) | | 5x-12=3x-6 | | 63x^2+10x-168=0 | | 8x=(56)(7) | | -2x=-1x | | -14x^2+47x+7=0 |